PERANAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) TERHADAP PENINGKATAN KESEJAHTERAAN PELAKU UMKM DI DESA TALANG DUKU KECAMATAN TAMAN RAJO KABUPATEN MUARO JAMBI - Jannah, Miftahul; Anita, Efni (Program Studi Manajemen Keuangan Syariah, 2024)
This research is motivated by the existence of problems faced by the people of Taman Rajo District, namely poverty, economic inequality and unemployment. The impact of Covid 19 on the income of Â Micro Small and Medium Enterprises has an impact on the welfare of the people of Muaro Jambi Regency. There are problems with the productivity of Micro Small and Medium Enterprises in Talang Duku Village which are suspected of not being able to improve the welfare of the local community. The research method used is a qualitative approach. The results of this study include: The role of Micro Small and Medium Enterprises in Talang Duku Village has created prosperity for owners of Micro Small and Medium Enterprises and increased the standard of living of the community. This can be seen from the 4 welfare indicators, namely high income, adequate education, proper housing and guaranteed health. In terms of Islamic financial management, the role of Micro Small and Medium Enterprises in improving the welfare of the people in Talang Duku Village can be seen from the allocation for health, education and decent livelihoods.